ACTIVITATEA ANTIFUNGICĂ A NOILOR DERIVAȚI VINIL- TRIAZOLICI CĂTRE FUSARIUM CULMORUM (W.G. SM.) SACC IN VITRO - Lupaşcu, Lucian; Gavzer, Svetlana; Cristea, Nicolae; Lupaşcu, Galina; Stîngaci, Eugenia; Zveaghinţeva, Marina; Sucman, Natalia; Macaev, Fliur (CEP USM, 2024)
Objectives: identification of new compounds with antifungal activity for the phytopathogenic fungus Fusarium culmorum. Methods: the isolation of F. culmorum strains was carried out in aseptic conditions on PDA (Potatoes Dextrose Agar) medium, with the subsequent identification of the species based on macro- and microscopic characteristics. Vinyl-triazole derivatives (D.V.T): EPS-165, MZ-115, MZ-118, EPS-23 were supplemented to the nutrient medium PDA in concentrations of 0,02; 0,01; 0,005; 0,0025; 0,00125%, sterilized by autoclaving. To assess the inhibitory effect of the studied preparations, the method of recording the diameter of the growing colonies was used. Results: the inhibitory effect of the studied preparations was specific depending on the concentration and the strain of the fungus investigated. The preparation MZ-118 offers wider opportunities for use in plant protection measures against the fungus F. culmorum. The factorial analysis demonstrated that in the system F. culmorum x D.V.T. x concentration, the main source of variation in fungal growth is D.V.T concentration. (50.2 ... 64.4%), followed by the isolate factor (24.7 ... 38.9%), which denotes the differential resistance of F. culmorum isolates to the action of the compounds under study.
ANTIFUNGAL ACTIVITY OF NEW VINYL-TRIAZOLE DERIVATIVES AGAINST FUSARIUM CULMORUM (W.G. SM.) SACC IN VITRO
Keywords: activity; concentrations; vinyl-triazole derivatives; fungi; activitate; concentrații; derivați vinil-triazolici